Changing demographic among Latino MSM diagnosed with HIV in Florida, 2007–2016. Issue 12 (2nd December 2019) - Sheehan, Diana M.; Auf, Rehab; Cyrus, Elena; Fennie, Kristopher P.; Maddox, Lorene M.; Spencer, Emma C.; Rosa, Mario De La; Trepka, Mary Jo
ABSTRACT: The study's objective was to assess temporal changes in birth country and age among newly diagnosed Latino men who have sex with men (MSM). We used records from Hispanics/Latinos (2007–2016) who were reported to the Florida HIV/AIDS surveillance system. We compared trends in birth country/region and age by year using a two-sided Cochran–Armitage Trend Test. Of 12, 427 new diagnoses, 85.9% were among men. Of men, 79.5% were MSM. The proportion attributable to MSM increased from 70.0% in 2007–85.7% in 2016 ( p -value < .0001). Compared with the trend in the proportion of MSM cases born in US-mainland, the proportion born in Cuba (20.0–29.9%; p -value < .0001) and South America (13.8% to 23.2%; p -value < .0001) increased significantly over time, and the proportion born in Central America (8.1% to 4.5%; p -value < .0001) decreased significantly over time. Compared with the trend in the proportion of MSM aged 35–49 years, the proportion aged 13–24 (15.4% to 20.6%; p -value < .0001) and 25–34 (25.0% to 35.6%; p -value < .0001) years increased significantly over time. In Florida, HIV prevention and screening strategies should be enhanced for Cuban and South American immigrants and young Latinos to address the increasing trend in new diagnoses among Latino MSM.